Proximate and micronutrient analysis of orange fleshed sweet potato leaves grown in Sylhet regions of Bangladesh - Kuddus, Mohammad Abdul; Miah, Md Mahbubul Alam; Datta, Gopal Chandra; Sarker, Ashoke Kumar; Alam, Mohammad Hasnal; Khan, Mohammad Mehedi Hasan (Research in Agriculture Livestock and Fisheries, 2020)
Sweet potato leaves are the traditional indigenous vegetables and most economically efficient source of micronutrients in terms of both land required and production costs per unit. This study aimed to compare and identify one variety rich with proximate, microelements and anti-oxidants from three high yielding sweet potato varieties viz. BARI SP-04, BARI SP -11 and BARI SP-12 including one local genotype leaves that helps provide leafy vegetables as well as micronutrients to poor community in lean vegetables production period of Sylhet regions. The tested varieties and genotype showed significant variation in different nutrient contents. In case of proximate composition the highest ether extract was found in BARI SP-11 (7.33% ±0.64 DW) and the lowest in BARI SP-04 variety (3.80% ± 0.42 DW). And the ash contents range was (12.05% ± 0.89 to 16.43% ± 1.02 DW), but the highest was recorded in BARI SP-12 and the lowest in BARI SP-04. In case of crude fiber the highest (19.99% ± 1.06 DW) was found in BARI SP-11 and the lowest (16.73% ± 0.62 DW) in local genotype. The microelements composition result revealed that BARI SP-04 reserved the highest (32.82 ± 4.5 mg 100 g-1) Iron & (2.1± 0.5 mg 100 g-1) Zinc and the lowest (19.40 ± 2.5 mg 100 g-1) Iron and (1.27 ± 0.2 mg 100 g-1) Zn in BARI SP-11 & local genotype respectively. However in case of phenolic compound, the highest 257.00 ± 10.3 mg TAE 100 g-1 DW was found in local genotype followed BARI SP-11 and BARI SP-12 but the lowest amount 218.75 ± 7.8 mg TAE 100g-1 DW was recorded in BARI SP-04. These results revealed that BARI SP-12 leaves reserved average standard proximate, microelements and antioxidant among the studied varieties and genotype. But all varieties leaves except local genotype contained essential nutrients which may favorably well to meet micronutrient deficiency especially lean vegetable production period for poor community in Sylhet region of Bangladesh. Res. Agric., Livest. Fish.7(1): 43-50, April 2020